2014
DOI: 10.4161/21624011.2014.946360
|View full text |Cite
|
Sign up to set email alerts
|

In situloading of skin dendritic cells with apoptotic bleb-derived antigens for the induction of tumor-directed immunity

Abstract: The generation and loading of dendritic cells (DC) ex-vivo for tumor vaccination purposes is laborious and costly. Direct intradermal (i.d.) administration of tumor-associated antigens could be an attractive alternative approach, provided that efficient uptake and cross-presentation by appropriately activated skin DCs can be achieved. Here, we compare the efficiency of i.d. delivery of relatively small apoptotic blebs (diameter »0.1-1 mm) derived from MART-1 transduced acute myeloid leukemia (AML) HL60 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Multiple studies have already reported on the ability of ApoEV-loaded DCs to induce antigen-specific CD8 + T cell responses [26,27,47]. Our unmodified ApoEVs were not able to induce robust MART-1 26–35 -specific CD8 + cell responses.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Multiple studies have already reported on the ability of ApoEV-loaded DCs to induce antigen-specific CD8 + T cell responses [26,27,47]. Our unmodified ApoEVs were not able to induce robust MART-1 26–35 -specific CD8 + cell responses.…”
Section: Discussionmentioning
confidence: 63%
“…An abundant source of both patient-specific neo-antigens and shared tumor-associated antigens (TAAs) for vaccination purposes, without the need for prior knowledge of the personalized epitope repertoire, is the autologous tumor itself. We previously showed that apoptotic extracellular vesicles (ApoEVs) derived from tumor cells can induce antigen-specific T cell responses both in vitro and ex vivo [26,27]. ApoEVs are produced when cells undergo apoptosis, resulting in membrane blebbing, membrane protrusion, and apoptotic body (ApoBD) formation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-derived “whole” cellular vaccines have therefore regained interest, especially with the recent insights in immunogenic cell death [ 21 ]. We have previously reported on the beneficial effects of using apoptotic AML-derived blebs as a source of TAA for in situ loading of skin DC [ 11 ], as well as MoDC loading in vitro [ 6 ]. As MoDC cultured in the presence of GM-CSF and IFNα have been described to have a higher capacity for the cross-presentation of antigens [ 13 , 14 , 22 , 23 ], they might constitute a more potent platform for the delivery of blebs in the context of DC vaccination strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, most DC subsets are capable of performing this task and appear to achieve this with similar efficacy [ 10 ]. Previously, we have reported that apoptotic blebs, derived from apoptotic AML cells, are a superior source of TAA for the in situ loading of human skin-resident DC, which take up and cross-present TAA from blebs to a higher degree as compared to ACR [ 11 ]. Moreover, IL-4 MoDC loaded with isolated apoptotic blebs increased CD4 + T cell proliferation and T helper (T H ) type I skewing (based on IFNγ production), as compared to using ACR; importantly, we have also shown that bleb-loaded IL-4 MoDC induce TAA-specific CD8 + T cells with higher avidity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy currently used is to load dendritic cells with tumor associated antigens, but the costs of generating these cells and treating them is extremely high. The use of skin tissue explants to load resident dendritic cells with tumor antigens in situ, has been successfully explored as an alternative method (Ruben et al 2014). Immune checkpoint inhibition has demonstrated promise in several malignancies, but successful treatment is dependent on infiltration of CD8 + T cells.…”
Section: B) Organoidsmentioning
confidence: 99%